Romantic Cemetery: Kolkata’s South Park Street Cemetery and Its Romantic Connections - Mukherjee, Souvik (Romanticism on the Net, 2021)
The South Park Street Cemetery in Kolkata (formerly Calcutta) is a popular tourist destination that houses the tombs of many key European figures from the period of East India Company rule. Some of these figures influenced British Romanticism in ways that were overt; others in ways that were less direct. In postcolonial India, however, although British Romanticism is still an important part of school and university curricula, the cemetery and the cultural history it contains are often forgotten. Of course, even the very existence of such colonial cemeteries has been under threat until recently, and the South Park Street Cemetery has lost its entire northern section. In a postcolonial India in which cemeteries have historically been under threat as vestiges of colonial rule that need to be erased and are neglected within classrooms where Romanticism is studied, it is important to highlight how they function as “contact zones” (Pratt). The cemetery serves as a physical index—and a reminder for mainstream research on Romanticism—of both the influence that Britain had on colonial India and India’s influence on British Romantic literature and culture. This article aims to (re)view Romanticism from this bipartite perspective and to explore how it is intertwined with the lesser-known stories that emerge from researching a colonial cemetery.